PENYULUHAN KESEHATAN TENTANG PROTOKOL KESEHATAN KAMPUS SEHAT DAN AMAN DARI PENYEBARAN COVID 19 MELALUI MEDIA VIDEO DAN BUKU PANDUAN DI STIKES SUAKA INSAN BANJARMASIN - Chrisnawati Chrisnawati; Anastasia Maratning; Margareta Martini; Gita Glory Sabatini (STIKES Suaka Insan Banjarmasin, 2022)
The era of the COVID-19 pandemic requires every educational institution to adapt in maintaining learning outcomes so that the quality of graduates remains optimal. Health education institutions try their best to use existing resources to provide educational services to students, although face-to-face learning can only be done through virtual face-to-face as well as laboratory and clinical practice. It has taken almost 2 years for the world of health education to undergo online learning, so the latest government regulation in 2022 calls for blended learning to be carried out immediately by combining lectures that are carried out face-to-face (50%) with face-to-face (50%). Educational institutions need to prepare the entire community to enter campus because it avoids the spread of the Covid-19 virus in the institutional environment. It is necessary to disseminate information by educational institutions to all students, lecturers and employees who work to pay attention to health rules and protocols. Health education on health protocols needs to be delivered in two forms of media, namely videos and guidebooks because they are very helpful in increasing knowledge that will affect attitudes in implementing health protocols on campus so that the spread of covid 19 can be avoided and campus as a place to learn and interact can be maximally functioned. by the academic community.